Peran Orangtua Terhadap Pemakaian Gadget pada Anak Dibawah Umur - Yan Pria Imsyaki Rhamadhani; Fauzi Permana; Annisa Tri Kartini; Sendi Ramadan (Cebong Journal, 2022)
Gadgets are tools that are used to communicate or are also used to find information and much more. Gadgets should not be used by small children. Because the impact of using gadgets on small children is very bad for their psyche. Parents should accompany the child when holding the gadget. Provide education or provide other things besides gadgets. If small children are addicted to gadgets, it will be difficult to direct them. In this scientific paper, we use qualitative research methods and interview data collection techniques. The results of the research that has been done on the use of gadgets by children are that children will lose respect for their parents, children will always depend on gadgets, children will forget their health and always play their gadgets.